A DESCRIPTIVE ANALYSIS OF SYSTEMATIC INVESTMENT PLANS: INVESTORS’ PERSPECTIVES (International Journal of Food and Nutritional Sciences, 2022)
Mutual funds mobilize savings from investors which are invested in a diversified portfolio of securities in capital and money market to generate good returns with the mitigation of risks involved in investment. SIP or Systematic Investment Plan is a plan offered by these mutual funds to inculcate the habit of savings and disciplined investment among public. SIP investments are increasing each month projecting an upward trend in future. However, there have been swings in the increasing trend due to high market volatility. Nevertheless, both individual and institutional investors are attracted towards SIP investments. SIPs allow investors to contribute fixed amount regularly at periodic intervals instead of lumpsum payments which beats the risks arising due to frequent market fluctuations. The SIP can be customized according to the requirements of investors and alterations can be made to existing SIP with higher flexibility compared to other mutual funds. SIPs can be made without any financial goal. But most of the investors invest in SIPs with specific investment goals such as dream home, education and marriage of children, tax savings and so on. The SIPs overcome risks related to inflation and market instability. Moreover, investors have greater control over investment. With the e-KYC facility, the investors can easily start SIP with the websites of fund house or AMCs. Investors can easily open Demat account for SIP by pre-deciding the investment amount, tenure and frequency of payment. The fixed amount that is automatically debited from savings account as per the standing instructions given to bank makes the investment more convenient for investor. This paper intends to provide an insight into the benefits offered by SIPs such as Rupee Cost Averaging and Compounding Power and other aspects related to SIPs which could be useful to beginners as well as existing investors.